Zuranolone – synthetic neurosteroid in treatment of mental disorders: narrative review - Marecki, Rafał; Kałuska, Joanna; Kolanek, Agata; Hakało, Dominika; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2023)
With each passing year, the number of people suffering from mental disorders grows at a disturbing speed. Neuroactive steroids are a new promising group of drugs with the potential for use in many diseases like postpartum depression, postnatal psychosis, major depression, insomnia, bipolar disorder, and Parkinson’s tremor, due to their ability to modulate the activity of GABAA receptor. Neurosteroids are progesterone metabolites that are synthesized from cholesterol or steroid hormones in various brain regions. They regulate neuronal development, regeneration, and neurotransmission. They are implicated in mood disorders, anxiety disorders, schizophrenia, PTSD, and impulsive aggression. Neurosteroids have been studied for their potential to prevent or treat neurodegenerative diseases such as Alzheimer’s disease and HIV-associated dementia. They can promote neurogenesis, neuronal survival, myelination, and memory function. They can also affect the growth and sensitivity of hormone-dependent brain tumors such as gliomas. Zuranolone, a newly registered neurosteroid drug has shown huge flexibility in both clinical and ambulatory treatment thanks to its pharmacokinetic traits, especially the possibility for oral administration, unlike its predecessor Brexanolone. Zuranolone is a synthetic positive allosteric modulator of the GABAA receptor that can be taken orally. The review aims to summarize the current knowledge on zuranolone as a novel neurosteroid drug for various mental disorders, especially for postpartum mental disorders for which this drug was meant originally. It covers studies indexed in the PubMed, Scopus, and Web of Science databases published since 2017. Keywords used in the search, as well as inclusion and exclusion criteria, are given in the aims and methodology section. The review explains the evidence for the role of neurosteroids, especially allopregnanolone, in the pathophysiology and treatment of postpartum depression. It discusses the mechanisms of neurosteroid action, the changes in neurosteroid levels during pregnancy and postpartum, and the clinical trials of brexanolone and zuranolone, two synthetic analogs of allopregnanolone, for postpartum depression. It provides an overview of the biosynthesis and metabolism of neurosteroids in the central and peripheral nervous system. Furthermore, it explains the different sources and pathways of neurosteroid production and the factors that influence their synthesis and regulation, such as stress, hormones, drugs, and genetic variations. The review also explores the potential relevance of neurosteroids for other psychiatric disorders, such as major depression, bipolar disorder, post-traumatic stress disorder (PTSD), schizophrenia, and premenstrual dysphoric disorder. Finally, it highlights the associations between neurosteroid levels and symptom severity and the effects of neurosteroid modulation on mood, cognition, and neuroplasticity.